Tutor facilitation in a PBL writing classroom through face-to-face group interactions - Aliyu, Muhammad Mukhtar; Yong, Mei Fung (LPPM Universitas Mercu Buana Yogyakarta, 2019)
Proficiency in writing in English has been a very important skill for undergraduates especially English as second language learners (ESL). However, it is the most challenging language skill to be acquired by the students not only in second (L2) or foreign language (FL) but also in the first language (L1). This is due to its complexity. Some scholars describe writing as a cognitive and social process. Various studies have been conducted on how to improve students’ writing skills. It is shown that supporting students in a writing process enhances their writing skills. For example, teachers are expected to give cognitive and social supports to students to allow them to improve their writing. This study reveals the strategies used by tutors in facilitating students’ writing process in a problem-based learning environment (PBL) through face-to-face group interactions. is one of the social media platforms found interesting and used by most of the students to interact with one another in and out of the school environment. It is used to provide social support to the students. An intact class of 18 second-year students in an English Composition course in Nigeria was selected in the study. The students were provided with a guide by tutors during the PBL writing process. Two tutors facilitated the students’ writing process in the PBL process. Tutor facilitation is one of the major components that facilitate meaningful learning in PBL. This is because, without proper guidance, students would end up in unfocused learning. Data were obtained through audio- and video-recording of students’ face-to-face interactions chats. The findings showed that the PBL tutors used various strategies to facilitate the participants’ writing such as open-ended questioning, metacognitive questioning, pushing students for an explanation, revoicing, summarizing, and generating/evaluating hypotheses. The support provided by the tutors helped the students to improve their writing. The findings of the study suggest some ways for teachers to improve students writing skills.